Purification, crystallization and preliminary X‐ray crystallographic analysis of diaminopimelate epimerase from Acinetobacter baumannii. Issue 1 (8th January 2013) - Park, Jeong Soon; Lee, Woo Cheol; Song, Jung Hyun; Kim, Seung Il; Lee, Je Chul; Cheong, Chaejoon; Kim, Hye‐Yeon
<x xml:space="preserve">Abstract</x> The meso isomer of diaminopimelate (meso‐DAP) is a biosynthetic precursor of L‐lysine in bacteria and plants, and is a key component of the peptidoglycan layer in the cell walls of Gram‐negative and some Gram‐positive bacteria. Diaminopimelate epimerase (DapF) is a pyridoxal‐5′‐phosphate‐independent racemase which catalyses the interconversion of (6S, 2S)‐2, 6‐diaminopimelic acid (LL‐DAP) and meso‐DAP. In this study, DapF from Acinetobacter baumannii was overexpressed in Escherichia coli strain SoluBL21, purified and crystallized using a vapour‐diffusion method. A native crystal diffracted to a resolution of 1.9 Å and belonged to space group P31 or P32, with unit‐cell parameters a = b = 74.91, c = 113.35 Å, α = β = 90, γ = 120°. There were two molecules in the asymmetric unit.